Frequency reconfigurable antenna for WLAN application. Issue 1 (January 2017) - Lim, M.C.; Rahim, S.K.A.; Hamid, M.R.; Eteng, A.A.; Jamlos, M.F.
ABSTRACT: This paper presents a frequency reconfigurable antenna fed by a coplanar waveguide (CPW). The antenna is able to switch between narrowband operation, centred at 5.8 GHz, and wideband operation in the range of 3.5 GHz to 5.97 GHz. It consists of an ellipse‐shaped wideband antenna integrated with a bandpass filter for narrowband operation. A pair of rectangular resonators with stubs is implemented at the ground plane to alter the electrical length.When a pair of integrated p‐i‐n diodes are turned OFF, a passband is realized in conjuction with two stopbands to suppress unwanted frequencies. On the other hand, wideband operation is realized when the end of the slot is shorted by eliminating the function of resonator. The overall size of the proposed antenna is 37.8 × 49 mm 2, inclusive of the DC biasing circuit. Simulated and measured for radiation pattern and reflection coefficient are carried out to compare the results. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:171–176, 2017